STUDI SALINITAS AIRTANAH DANGKAL DI KECAMATAN ULUJAMI KABUPATEN PEMALANG TAHUN 2012 - Indahwati, Nur (Pendidikan Geografi, 2013)
ABSTRACTThe aims of this research are to: (1) know spatial distribution of salinity, (2) determine the relationship between coastline distances with salinity of groundwater, (3) measure the deepness of salt water interface in Ulujami Subdistict 2012.This research uses descriptive quantitative method. The populations are the shallow groundwater that is showed by dug wells in Ulujami Subdistict. The sampling technique was done by making transect line system.Based on the results, it can be concluded: (1) the spatial distributions of salinity in Ulujami Subdistict have been concentrated in the north area/ nearby coastline, (2) there is a negative relationship between coastline distances with salinity of groundwater in Ulujami Subdistict. (3) the deepness of salt water interface in Ulujami Subdistict will increase along with it?s distance from coastline.Keywords: salinity, electric conductivity, distance, interface